Penerapan PSAK No. 34 Dalam Pengakuan Pendapatan Jasa Konstruksi Pada PT. Praja Suwito Borneo Di Serdang Bedagai - Nur Mellia Syahdila; Porkas Sojuangon Lubis; Widia Wardani (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
The aim of the research is to determine whether financial reporting for revenue recognition in construction companies is in accordance with PSAK No. 34. To collect data, the author used field research techniques, namely through interviews with leaders, employees or company finance, and documentation. Meanwhile, for data analysis techniques, the author uses qualitative descriptive. This research was conducted at PT. Praja Suwito Borneo which is located on Jalan Medan-Tebing (Simp. Matapao) Liberia Village, Teluk Mengkudu District, Serdang Bedagai Regency, North Sumatra Province. Based on the results of the research and discussions that have been carried out, it is concluded that the income recognition implemented by PT. Praja Suwito Borneo is not yet fully compliant with PSAK No. 34. This can be seen from the activities of companies that use the cash basis method, namely where income is recognized when payment is received.